Are organic acids really related to the sour taste difference between Chinese black tea and green tea?. Issue 6 (19th April 2022) - Zhang, Xiang; Du, Xiao; Li, Ying‐zheng; Nie, Cong‐ning; Wang, Cong‐ming; Bian, Jin‐lin; Luo, Fan
Abstract: Sour is an important taste in some foods, beers, and teas; organic acids, in particular, are thought to play a key role in the formation of the sour taste of beer. It has been generally thought that organic acids also contribute to some teas tasting sour. In this study, through sensory evaluation experiments with black tea (BT) and green tea (GT), the difference in the sour taste of BT and GT was quantitatively characterized. Then the organic acids in the two types of tea were identified and quantified via high‐performance liquid chromatography (HPLC) with taste activity value (TAV) analysis. The results showed that both teas had 12 identical common organic acids (including 11 taste‐active components), but the results of the TAV analysis were not consistent with those of the sensory evaluation. Therefore, there is no direct relationship between organic acids and the acidity in BT and GT. It is related to the interaction between organic acids and other substances, pH value, or other sour substances in tea infusions. The mechanism of the disappearance of sourness in tea infusions was also discussed. These results help us to understand the correlation between tastes in teas. Abstract : Organic acid is one of the important taste substances in tea infusions. In this study, the acidity and organic acid content of black tea (BT) and green tea (GT) were studied and it was found that the acidity in BT and GT was not directly related to organic acids, but was related to the interaction between other sour substances. The mechanism of the disappearance of sour in tea was discussed, which may be due to the masking or retronasal sniffing.